Structural Integration Case Report: a Global Intervention Challenging the Limitations of Local Rehabilitation - Landels, Bachelor of Health Studies, Bernice (International Journal of Therapeutic Massage & Bodywork, 2020)
Background: Conventional rehabilitation for musculoskeletal injuries postsurgery is generally site-specific and aims to return the person to ‘normal’ function. Commonly, conventional treatment focuses locally and little or no attention is given to comorbidities, other symptoms, postural compensations, or adaptations either pre-existing or resulting from the injury. Structural Integration (SI) is a manual therapy applied to and focusing on fascial continuities throughout the whole body. This case report explores SI as a global, whole-body intervention for rehabilitation. Purpose: To examine the effects of a whole-body approach that addresses local and global symptoms following ankle surgery. Methods: The Anatomy Trains Structural Integration (ATSI formerly KMI) 12-series protocol was applied and a selection of outcome measures were used to track progress and assess the eff icacy of SI. Ankle mobility and function was assessed primarily using Weight-Bearing Lunge Test and Lower Extremity Functional Scale. Local pain was reported using the McGill Pain Questionnaire. General wellbeing was evaluated using subjective questioning and the WHO Quality of Life Questionnaire. Results: Local results included increased mobility and function to affected leg, and reduced pain and swelling. Global results included an improvement in physical and psychological well-being, with the reduction of pain and dysfunction in other areas. Conclusion: This case report demonstrates global benefits of a whole-body approach when structural integration is applied during rehabilitation. More clinical research that includes SI is needed to determine if the local and global results shown in this case study can be demonstrated in additional rehabilitation populations.